When the microbiome meets One Health principle: Leading to the Holy Grail of biology and contributing to overall well‐being and social sustainability - Yazhou Zhou; Ziying Xu; Huan Zhang; Teng Liu; Jin Zhou; Yujing Bi; Yanping Han; Yafang Tan; Jing Yuan; Ruifu Yang (iMetaOmics)
Abstract The convergence of microbiome science with the One Health principle heralds a transformative era in biology, prioritizing the collective well‐being of humans, animals, and the environment. This review delves into the intricate dance between microbiomes and their hosts, revealing their profound impact on health, nutrient cycles, and climate change. Championing a unified approach to health issues across diverse kingdoms of life, One Health emerges as a holistic strategy, underscored by a proposed universal balance theory, “Balance of Dynamic Factors.” This theory spotlights the equilibrium within microbial and human‐animal‐environment interactions, offering a revolutionary pathway to global health and social well‐being. It paves the way for disease prevention, health equity, and sustainability, all of which are purviews of a balanced ecological system. We navigate the challenges and opportunities of this integrative approach, culminating in a call for action for the incorporation of microbiome science into health policies, precision medicine, legislation, eco‐health projects, and education, thereby setting the stage for harmonious coexistence with our planet.